Development of STEM-based interactive e-module on ecology topic for senior high schools’ student - Rizqi Fauzi; Adieba Warda Hayya (Department of Biology Education, Universitas Pendidikan Indonesia, 2022)
The quality of education must always be improved to get maximum results. One way to improve it is by developing learning media. Based on the results of field observations in this study at MA Raudlatus Shibyan, the use of learning media was still not optimal. For this reason, researchers developed an Interactive E-module product containing Ecology topic in Biology Learning as a supplement to learning. An interactive e-module is an electronic module that contains materials, videos, audio, animations, quizzes, and evaluations, which allow students to study independently. This descriptive research consists of three main stages, include Planning, Project, Evaluation (PPE). The interactive e-module developed was compiled using the Canva web, then the file was saved as a PDF, after which editing was continued using the Flip PDF Professional application. The product was then validated by a material expert and got a percentage score of 98.12% in the